Hearing impairment and ear anomalies in craniofacial microsomia: a systematic review. Issue 10 (October 2022) - Rooijers, W.; Tio, P.A.E.; van der Schroeff, M.P.; Padwa, B.L.; Dunaway, D.J.; Forrest, C.R.; Koudstaal, M.J.; Caron, C.J.J.M.
Abstract: The aim of this systematic review was to review the literature on hearing impairment and ear anomalies in patients with craniofacial microsomia and to determine their prevalence. Sixty-two records including 5122 patients were included. Ear anomalies were present in 52–100% of patients. The most reported external ear malformations were microtia, pre-auricular tags, and atresia of the external auditory canal. Ossicular anomalies were the most reported middle ear malformations, whereas the most reported inner ear malformations included oval window anomalies, cochlear anomalies, and anomalies of the semicircular canals. Hearing loss in general was reported in 29–100% of patients, which comprised conductive hearing loss, mixed hearing loss, and sensorineural hearing loss. Between 21% and 51% of patients used hearing aids, and 58% underwent a surgical intervention to improve hearing. The relationship between different phenotypes of craniofacial microsomia and the type and severity of hearing loss is mostly unclear. In conclusion, the high prevalence of ear and hearing anomalies in patients with craniofacial microsomia underlines the importance of audiological screening in order to facilitate individual treatment.